Media Digital dan Interaktif: Metodologi Pendidikan Interaktif Berbasis Platform Digital - Ria Ratna Ningtyas; Ima Rosila; Rahmat Kamal (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the urgency of reconstructing interactive and digital-based educational methodologies as a solution to face the ever-changing developments of the times. By looking at the challenges of stagnant traditional education, such as methodological conservatism and lack of utilization of technology, this article uses the Systematic Literature Review (SLR) method to explore various studies related to the use of digital platforms in education. Through an analysis of digital media such as Kahoot! and Duolingo, it highlights how interactive features can increase student engagement, motivate learning, and strengthen critical thinking. Some solutions to overcome the problems of digital media education include; improving technological infrastructure, digital competency training for teachers, and integrating technology with the curriculum as a whole.